Major features of Municipal Finance in Bangladesh: A Case Study Based Investigation - Reza, Farhadur; Hossain, S M Nawshad; Miti, Sania Sifat; Haq, Md Enamul (Journal of Bangladesh Institute of Planners, 2015)
The rapid increase in the urban population has put pressure on local governments to provide a range of services from water and sewer infrastructure to social services and housing. The extent to which a municipality is able to deliver services efficiently depends on its level and nature of finance. To cope with rapid urbanization and provide basics services, municipalities need to adopt efficient financial management system. This paper addresses the major features of municipal finance (revenue and expenditure) of Taherpur and Noahata Municipalities and proposes some guidelines to enhance their financial management system. Data on municipal revenue and expenditure were collected from annual budgets of the Taherpur and Noahata Municipality. The study findings state that, Municipalities, for their revenue are largely dependent on government grant, local and foreign fund for development sector; whereas general establishment and infrastructural development are prime expenditure items. The paper also proposes some guidelines to enhance financial management system of the Municipalities. Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 103-109